Pulse frequency modulation based tri-mode controller for switched-mode DC-DC converters - Nashit, Salma (2016)
This thesis pertains to the analysis and design of low-power and low output ripple-voltage multi-mode switched-mode DC-DC converter based on the Pulse Frequency Modulation (PFM). The applications of the DC-DC converter are low-power portable electronic devices, such as smartphones, tablets, notebooks, etc. These devices often operate at the standby condition—where the load current is relatively low—and thus, the power-efficiency at such a condition is paramount to extend the battery lifespan.